Analysis of sedative-hypnotic drug use trends in children and adolescents (2018–2023): a study based on outpatient prescription data from a general hospital - Qingyu, Zhang; Wenqing, Jiang; Le, Ma; Yanbin, Hou; Pingping, Miao; Chen, Lin; Jiaxin, Mao; Ni, Dai; Dalu, Yang; Kanzhen, Tong; Junting, Su; Zhenzhen, Zhu; et al. (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to analyze the use of sedative-hypnotic drugs among children and adolescents in a hospital setting, providing a reference for optimizing drug use.MethodsA retrospective analysis was conducted on the prescription data of sedative-hypnotic drugs for children and adolescents aged 6–18 years from 2018 to 2023 at the outpatient department of the hospital. Data were organized using Excel and analyzed using statistical software such as SPSS, with descriptive statistics and independent samples t-tests used to analyze medication patterns across different age groups and genders.ResultsThe majority of prescriptions originated from the psychiatry department. The most common diagnoses included depressive state, anxiety state, and sleep disorders. Combination therapy with benzodiazepines and antidepressants was the most common treatment regimen. The number of prescriptions showed a yearly increasing trend, rising from 160 in 2018 to 1,583 in 2023, and the total usage also increased annually, from 30.47 g in 2018 to 260.15 g in 2023. Despite the increase in total usage, the drug usage per prescription decreased year by year. Most patients had a medication duration of less than 30 days, and the per capita usage increased with longer medication durations. Lorazepam and zopiclone were the most frequently used drugs. The study also found that the duration of medication use was significantly longer in female patients than in males, and significantly longer in the 6–12 age group compared to the 13–18 age group.ConclusionThe use of sedative-hypnotic drugs in children and adolescents has shown a yearly increasing trend, and the management of sedative-hypnotic drug use in children and adolescents should be strengthened.